Review of the Reported Measures of Clinical Validity and Clinical Utility as Arguments for the Implementation of Pharmacogenetic Testing: A Case Study of Statin-Induced Muscle Toxicity - Jansen, Marleen E.; Rigter, T.; Rodenburg, W.; Fleur, T. M. C.; Houwink, E. J. F.; Weda, M.; Cornel, Martina C. (Frontiers in Pharmacology, 2017)
Advances from pharmacogenetics (PGx) have not been implemented into health care to the expected extent. One gap that will be addressed in this study is a lack of reporting on clinical validity and clinical utility of PGx-tests. A systematic review of current reporting in scientific literature was conducted on publications addressing PGx in the context of statins and muscle toxicity. Eighty-nine publications were included and information was selected on reported measures of effect, arguments, and accompanying conclusions. Most authors report associations to quantify the relationship between a genetic variation and outcomes, such as adverse drug responses. Conclusions on the implementation of a PGx-test are generally based on these associations, without explicit mention of other measures relevant to evaluate the clinical validity and clinical utility. To gain insight in the clinical impact and select useful tests, additional outcome measures are needed to estimate the clinical validity and utility, such as cost-effectiveness.